Comparative analysis of the chicken IFITM locus by targeted genome sequencing reveals evolution of the locus and positive selection in IFITM1 and IFITM3 - Bassano, Irene; Ong, Swee Hoe; Sanz-Hernandez, Maximo; Vinkler, Michal; Kebede, Adebabay; Hanotte, Olivier; Onuigbo, Ebele; Fife, Mark; Kellam, Paul (BMC genomics, 2019)
BACKGROUND: The interferon-induced transmembrane (IFITM) protein family comprises a class of restriction factors widely characterised in humans for their potent antiviral activity. Their biological activity is well documented in several animal species, but their genetic variation and biological mechanism is less well understood, particularly in avian species. RESULTS: Here we report the complete sequence of the domestic chicken Gallus gallus IFITM locus from a wide variety of chicken breeds to examine the detailed pattern of genetic variation of the locus on chromosome 5, including the flanking genes ATHL1 and B4GALNT4. We have generated chIFITM sequences from commercial breeds (supermarket-derived chicken breasts), indigenous chickens from Nigeria (Nsukka) and Ethiopia, European breeds and inbred chicken lines from the Pirbright Institute, totalling of 206 chickens. Through mapping of genetic variants to the latest chIFITM consensus sequence our data reveal that the chIFITM locus does not show structural variation in the locus across the populations analysed, despite spanning diverse breeds from different geographic locations. However, single nucleotide variants (SNVs) in functionally important regions of the proteins within certain groups of chickens were detected, in particular the European breeds and indigenous birds from Ethiopia and Nigeria. In addition, we also found that two out of four SNVs located in the chIFITM1 (Ser36 and Arg77) and chIFITM3 (Val103) proteins were simultaneously under positive selection. CONCLUSIONS: Together these data suggest that IFITM genetic variation may contribute to the capacities of different chicken populations to resist virus infection.
Keywords: DNA Copy Number Variations; kur domácí; Animals; Genetic Loci; sekvenční homologie; Chickens; mapování chromozomů; sekvence aminokyselin; jednonukleotidový polymorfismus; Chromosome Mapping; variabilita počtu kopií segmentů DNA; selekce (genetika); Polymorphism, Single Nucleotide; genom; Genome; Evolution, Molecular; Amino Acid Sequence; molekulární evoluce; diferenciační antigeny; Selection, Genetic; Sequence Homology; Antigens, Differentiation; Sequence Analysis, DNA; zvířata; genetické markery; sekvenční analýza DNA; genetické lokusy; Genetic Markers